2014
DOI: 10.5588/pha.14.0047
|View full text |Cite
|
Sign up to set email alerts
|

Do incentives improve tuberculosis treatment outcomes in the Republic of Moldova?

Abstract: Provision of incentives to TB patients significantly improved treatment success rates and needs to continue. Treatment retention increased, thus potentially preventing drug resistance, a serious problem in the Republic of Moldova.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 2 publications
7
48
0
2
Order By: Relevance
“…The other studies (n = 8) occurred in countries out of this category, but referred to as low-income: Malawi 21 Quasi-experimental designs (n = 11) accounted for most of the reviewed studies, followed by RCTs (n = 9) and observational studies (n = 5). Seventeen studies (among then eight RCTs) presented evidences on effects of non-financial interventions for TB patients (lay community health workers or social workers 19,28,31,32,33,34,35 , food assistance 23,27,28,30,36,37 , counselling 22 , "TB clubs" 20 , training programs 26 , social franchising 38 , socio-educational approaches 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other studies (n = 8) occurred in countries out of this category, but referred to as low-income: Malawi 21 Quasi-experimental designs (n = 11) accounted for most of the reviewed studies, followed by RCTs (n = 9) and observational studies (n = 5). Seventeen studies (among then eight RCTs) presented evidences on effects of non-financial interventions for TB patients (lay community health workers or social workers 19,28,31,32,33,34,35 , food assistance 23,27,28,30,36,37 , counselling 22 , "TB clubs" 20 , training programs 26 , social franchising 38 , socio-educational approaches 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies presented patient or treatment supporters directed financial interventions (among then seven quasi-experimental studies), including monetary incentives 22,24,25,27,28,29,35,39,40,41 , a conditional cash transfer program 42 and economic support by voucher delivery 43 . Some studies 22,27,28,35 combined financial and non-financial interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…self-administered treatment [SAT] versus supervised treatment).TB treatment outcomes were more likely to be successful in patients who were supervised than in SAT patients. ‘ TB patients are now not given an option of self-supervision. They are rather assigned to a DOT provider supported by the Ministry of Health.’ Ciobanu A. et al (2014), Moldova [28]Retrospective cohort study using data from the national electronic patient database and incentive registers. The study objective was to compare treatment outcomes among new drug-susceptible TB patients registered for treatment before 2008 and after the 2011 introduction of incentives.Provision of incentives to TB patients significantly improved treatment success rates and needs to continue. ‘ The published study was the basis for the National Tuberculosis Program to mobilize financial sources both from the national budget sources as well as the Global Fund to fund incentives for TB patients.’ Mahajan R. et al (2015), India [29]This retrospective analysis included all patients with confirmed HIV-visceral leishmaniasis (VL) coinfection receiving combination treatment for VL at a MSF treatment centre between 2012 and 2014.Combination therapy appeared to be well tolerated, safe and effective, and may be considered as an option for treatment of VL in HIV co-infected patients.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, policy and/or practice change is a complex phenomenon as various factors could contribute to change. While it is practically difficult to decipher the contribution of specific factors, we speculate on the following reasons for this positive linkage: (1) some participants were working in programme settings in close liaison with the key policy stakeholders that enhanced their direct role in fostering change; (2) the identification of programme relevant research questions right at the start; and (3) early engagement of policy makers and programme managers from the stage of formulation of the research question until it was published [28,29]. These are favourable factors in englobing research results within a conducive environment for fostering absorption of study findings and eventual contribution towards policy/and or practice change.…”
Section: Discussionmentioning
confidence: 99%